2021
DOI: 10.21037/tcr-21-526
|View full text |Cite
|
Sign up to set email alerts
|

Systematically integrative analysis identifies diagnostic and prognostic candidates and small-molecule drugs for lung adenocarcinoma

Abstract: Background: Lung adenocarcinoma (LUAD) is the most common histological subtype of lung cancer (LC).However, the early-stage diagnostic rate is still low, and the 5-year overall survival (OS) rate remains poor. The present study aimed to identify critical genes as diagnostic and prognostic markers and small-molecule drugs for combating LUAD using a systematic bioinformatics analysis.Methods: Five gene expression profiling datasets were systematically integrated and analyzed. First, gene coexpression modules wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…Developing a robust prognostic signature is very important to effectively predict the survival of LUAD patients. In recent years, many types of molecular prognostic signatures have been developed, including protein, mRNA, miRNA and lncRNA [6][7][8][9][10]. Some signatures have also showed better predictive capability [38,39,42,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing a robust prognostic signature is very important to effectively predict the survival of LUAD patients. In recent years, many types of molecular prognostic signatures have been developed, including protein, mRNA, miRNA and lncRNA [6][7][8][9][10]. Some signatures have also showed better predictive capability [38,39,42,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the high heterogeneity of LUAD, the prognoses of LUAD patients within the same TNM group presented heterogeneous outcomes [6], which suggests that some new prognostic methods should be developed and used to refine risk stratification, such as molecular prognostic marker [6]. In recent years, with the progress of molecular biology, some molecular prognostic markers including protein, mRNA, miRNA, lncRNA, and oncogene were identified [6][7][8][9][10]. In addition, liquid biopsies based on circulating tumor cells (CTCs) and circulating free DNA (cfDNA) and tumor microenvironment (TME) based on tumor-infiltrating immune cells (TICs) are of much interest to many scientists in predicting the survival, and some valuable results have been obtained [6,11,12].…”
Section: Agingmentioning
confidence: 99%
“…To date, ANXA3 has been found to not only maintain genomic integrity and facilitate cell proliferation and differentiation but also contributes to tumor initiation and growth. We synthesized the relevant literature and found that that ANXA3 expression was dysregulated in a large number of tumor populations, such as bladder urothelial carcinoma ( 23 ), BRCA ( 17 ), CHOL ( 16 ), COAD ( 24 ), esophageal carcinoma ( 25 ), head and neck squamous cell carcinoma ( 26 ), kidney chromophobe ( 27 ), kidney renal papillary cell carcinoma ( 28 ), hepatocellular carcinoma ( 29 ), LUAD ( 30 ), LUSC ( 31 ), pancreatic adenocarcinoma ( 32 ), PRAD ( 33 ), READ ( 34 ), stomach adenocarcinoma ( 25 ), thyroid carcinoma ( 35 ), and uterine corpus endometrial carcinoma ( 13 ). In this study, an increased ANXA3 expression was associated with a favorable prognosis, suggesting that ANXA3 might play a pivotal role in decreasing cancer risk in patients with OV.…”
Section: Discussionmentioning
confidence: 99%